1992
DOI: 10.1136/hrt.68.9.291
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of myocardial ischaemia: the benefit of a fixed combination of atenolol and nifedipine in patients with chronic stable angina

Abstract: Objective-To study the effects on myocardial ischaemia of 50 mg of atenolol, 20 mg of slow release nifedipine, and their fixed combination given 12 hourly.Design-A treadmill exercise test and 24 hour ambulatory electrocardiographic monitoring were carried out after a period of five days off treatment (control) and at the end of three weeks of each treatment period.Patients-23 patients with stable angina pectoris, documented coronary artery disease, and a positive exercise test were randomised in a double blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…There were 28 studies (37 comparisons) of a CCB added to a BB ( n = 2468); 7–35 12 studies (12 comparisons) of a BB added to a CCB ( n = 1489); 9,11,12,1416,19,20,24,25,29,34 7 studies (8 comparisons) of a LAN added to a BB or CCB ( n = 329); 7,3640 3 studies (4 comparisons) of ranolazine added to a BB or CCB ( n = 1388); 41–43 8 studies (9 comparisons) of trimetazidine added to a BB or CCB ( n = 2875); 4451 1 study of ivabradine added to a BB ( n = 889). 52 No studies were found that evaluated the impact of nicorandil in an add-in role on either ETT or clinical measures of anti-anginal efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…There were 28 studies (37 comparisons) of a CCB added to a BB ( n = 2468); 7–35 12 studies (12 comparisons) of a BB added to a CCB ( n = 1489); 9,11,12,1416,19,20,24,25,29,34 7 studies (8 comparisons) of a LAN added to a BB or CCB ( n = 329); 7,3640 3 studies (4 comparisons) of ranolazine added to a BB or CCB ( n = 1388); 41–43 8 studies (9 comparisons) of trimetazidine added to a BB or CCB ( n = 2875); 4451 1 study of ivabradine added to a BB ( n = 889). 52 No studies were found that evaluated the impact of nicorandil in an add-in role on either ETT or clinical measures of anti-anginal efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…The combination is better than felodipine monotherapy el-Tamimi and Davies [18] Atenolol 50 mg/day + nifedipine SR 20 mg/day vs atenolol vs nifedipine SR Suboptimal β-blockade (n = 23) Combination better than metoprolol for time to 1mm STD, STD at highest comparable workload, and maximal STD.…”
Section: Trials Indicating a Favorable Results For Combination Therapymentioning
confidence: 99%
“…However, differences in patient selection, study design, and drug dosages all prevent critical comparisons. Specific comparisons were β blockers and dihydropyridines,67 68 69 70 71 β blockers and diltiazem or verapamil,72 73 74 and studies with three drugs 75 76. Within the time frame of our search there was no compelling evidence to choose one β blocker over another (I) 77 78 79.…”
Section: Age Limitsmentioning
confidence: 99%
“…Adding dihydropyridines to β blockers produces a dose dependent improvement in exercise tolerance (I)71 111 112 113 114 115 116 117 and adding diltiazem to β blockers produces a dose dependent improvement in symptom control and exercise tolerance (I) 74 117 118. If this second combination is used the cautions in the British National Formulary should be observed 47.…”
Section: Age Limitsmentioning
confidence: 99%